How to generalize Darwinism suitably to help understand both the evolution and the development of economies - Pavel Pelikan (Max Planck Institute of Economics, 2008)
This paper agrees that a suitably generalized Darwinism may help understand socioeconomic change, but finds the most publicized generalization by Hodgson and Knudsen unsuitable. To do better, it generalizes the extension of Neo-Darwinism into evolutionary developmental biology (evo-devo), which pays more attention to genomes-as-instructors than to genes-as-replicators, and to the entire process of instructed development than to fully developed organisms. The new generalization has clear connections to economics with a minimum guarantee of helpfulness: it generalizes both evo-devo and previously elaborated approaches that already helped understand specific issues of comparative economics, economic reforms, and transformation policies.
Keywords: A10; D02; K10; O10; P50; Z10; 330; evolution of instructions; instructed development of interactors; multilevel evolution and development; evolution of institutional rules; development of economies